When calls the heart. In like a lion & Turn of the page [videorecording (DVD)] - Landon, Michael, 1964-; Krakow, Erin; Wagner, Jack, 1959-; Hutton, Pascale; McGarry, Kevin, 1985- (Shout!, 2022)
In Like A Lion finds Elizabeth returning to her beloved Hope Valley after a month away and discovering that some surprising changes have occurred in her absence. From a mayoral race to exciting business ventures to old friends in new roles in the community, the one constant for Elizabeth is her budding romance with Lucas Bouchard. Then, in Turn Of The Page, the long-awaited arrival of Elizabeth's novel should be cause for celebration, but hurt feelings and negative reviews threaten to put a damper on her accomplishment.